Availability Degree of Visual Thinking Skills in Science Curriculum for Fourth Basic Grade in Syrian Arab Republic (Journal of Hama University, 2026)
The aim of the research was to analyze the content of the science book for the fourth basic grade to identify the extent to which it includes visual thinking skills. The researcher used the content analysis method from the descriptive approach, and the research sample consisted of the science book for the second semester, which includes only three units and is prescribed for the fourth basic grade by the Syrian Ministry of Education for the academic year 2024/2025. The research tool was an analysis card for visual thinking skills, based on a list prepared by the researcher. The researcher reached the results that the most included visual thinking skills in the science textbook (Chapter Two) for the fourth grade are the skill of (analyzing the visual shape) with a frequency of (60) and a high inclusion rate of (32.79%). The second rank is occupied by the skill of (extracting meanings from the visual shape), which has a frequency of (50) and a high inclusion rate of (27.32%). The third and fourth ranks are held by the skills of (the ability to recognize and describe the shape, and connecting relationships in the visual shape) with frequencies of (39) and (31) and a medium inclusion rate of (21.31%) and (16.94%), respectively. Finally, the skill of (perceiving and interpreting ambiguity from the visual shape) has a frequency of (3) and a low inclusion rate of (1.64%).Based on these results, the researcher presented several suggestions, the most important of which are: paying attention to visual thinking skills in similar proportions in the science textbook, and training teachers in visual thinking skills.
Keywords: Visual Thinking Skills, Science Curriculum, Fourth Basic Grade.